GESTÃO DEMOCRÁTICA NO MARANHÃO: UMA ANÁLISE DO CADERNO DE ORIENTAÇÕES PEDAGÓGICAS DO PROGRAMA ESCOLA DIGNA - SILVA, Raul Sousa (2025)
Democratic management is a constitutional and educational principle ensured by legal provisions such as the 1988 Federal Constitution, the Law of Guidelines and Bases of National Education (Law No. 9.394/1996), and the National Education Plan (Law No. 13.005/2014). In Maranhão, the Escola Digna Program is a public policy aimed at strengthening democratic management in state public schools. This dissertation aims to analyze the Pedagogical Guidelines Booklet of the Escola Digna Program in order to identify and discuss the democratic management elements present in the document. The research adopts a qualitative approach, based on a bibliographic survey, a state-of-the-art review, and document analysis. The results indicate that the booklet proposes guidelines and actions aimed at encouraging school community participation, valuing collective school leadership, and promoting continuous training for education professionals. Despite its advances, limitations are observed in the practical implementation of the proposed guidelines. As an educational product, a collection of practical guides was developed to support the implementation of democratic practices in public schools in the state.